PELATIHAN PENGOLAHAN ALPUKAT MENJADI KERUPUK - Hairun, Yahya; Tonra, Wilda Syam; Abdullah, In .Hi; Ikhsan, Muhammad (Jurnal Terapan Abdimas, 2022)
Abstract. This Community Service (PkM) aims to provide training for inhabitant of Tidore Islands, Afa-Afa Village, to process avocados into crackers. Avocado was chosen because this fruit is very abundant in Afa-afa, even avocados often rot when the harvest season comes, another reason because this fruit has a high nutritional value. Therefore, this activity is the initiation of processing avocados into products that have a higher economic value or selling value. This training was held on July 24, 2021. The parties involved were the PkM team from Khairun University, Inhabitant of afa-afa Village. The number of participants is 24. PkM method are the opening ceremony, presentation of training materials, discussions for sharing between presenters and participants, as well as direct demonstrations on how to make crackers. Second, the product is avocado crackers. There are two results of this PkM, first is the description of the method and the description of the product. The product is avocado crackers. The hallmark of this crackers is the presence of a bitter taste in the crackers, the way to counteract the bitter taste is to add sugar to the cracker dough or you can also add wet sugar after the crackers are fried.Abstrak. Kegiatan pengabdian kepada Masyarakat (PkM) ini bertujuan untuk memberikan pelatihan kepada masyarakat Kepulauan Tidore Keluarahan Afa-Afa guna mengolah alpukat menjadi kerupuk. Alpukat dipilih karena buah ini sangat melimpah di daerah Afa-afa, bahkan seringkai buah alpukat membusuk jika musim tiba, alasan lain karena buah ini memiliki nilai gizi yang tinggi. Oleh karena itu kegiatan ini sebagai inisiasi pengolahan alpukat menjadi produk yang memiliki nilai ekonomis atau nilai jual yang lebih tinggi. Pelatihan ini dilaksanakan pada tanggal 24 Juli 2021. Pihak yang terlibat adalah tim  PkM dari Universitas Khairun, pihak kelurahan afa-afa dan PKK Afa-afa. Jumlah peserta adalah 24 orang. Metode Pelaksanaan PkM adalah pembukaan, presentasi materi pengolahan kerupuk, diskusi dengan peserta pelatihan, demonstrasi pembuatan kerupuk. Hasil dari kegiatan ini berupa deskripsi tentang pelaksanaan kegiatan dan deskripsi tentang produk berupa kerupuk alpukat. Ciri khas dari produk kerupuk alpukat ini adalah adanya rasa pahit pada kerupuk, cara untuk mentaktisi rasa pahit adalah pemberian gula pada adonan kerupuk atau bisa juga memberikan gula basah setelah kerupuk digoreng.